2016
DOI: 10.1093/rheumatology/kew308
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of NICE quality standards for patients with new presentation of inflammatory arthritis: observations from the National Clinical Audit for Rheumatoid and Early Inflammatory Arthritis

Abstract: The audit has highlighted gaps between NICE standards and delivery of care, as well as substantial geographic variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
1
13
1
1
Order By: Relevance
“…Most significant delays to therapy occur due to delays in access to rheumatology, and time-to-DMARD start once a patient is seen by a rheumatologist is often negligible (26), a finding confirmed by our study. In comparison, wait-time benchmarks for DMARD start times are more stringent in our Canadian set than in the NICE quality standards from the UK, yet higher rates of adherence are reported in our study (75% within 14 days of diagnosis in CATCH compared to 53% treated within 6 weeks of referral in the UK) (27). Unfortunately, the complementary measure of waiting time to rheumatology care, that captures the time between rheumatologist referral and first visit for patients with RA (7), was not captured in CATCH and is being evaluated in other data sources, including triage databases across the country.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Most significant delays to therapy occur due to delays in access to rheumatology, and time-to-DMARD start once a patient is seen by a rheumatologist is often negligible (26), a finding confirmed by our study. In comparison, wait-time benchmarks for DMARD start times are more stringent in our Canadian set than in the NICE quality standards from the UK, yet higher rates of adherence are reported in our study (75% within 14 days of diagnosis in CATCH compared to 53% treated within 6 weeks of referral in the UK) (27). Unfortunately, the complementary measure of waiting time to rheumatology care, that captures the time between rheumatologist referral and first visit for patients with RA (7), was not captured in CATCH and is being evaluated in other data sources, including triage databases across the country.…”
Section: Discussioncontrasting
confidence: 59%
“…Unfortunately, the complementary measure of waiting time to rheumatology care, that captures the time between rheumatologist referral and first visit for patients with RA 7, was not captured in CATCH and is being evaluated in other data sources, including triage databases across the country. In the UK, adherence to the NICE quality standard wait‐time benchmark of 3 weeks for rheumatologist consultation was poor (38%) 27, likely contributing to the lower rates of timely treatment seen, as the measure for time‐to‐treatment was anchored at the referral date.…”
Section: Discussionmentioning
confidence: 99%
“…The RA-QUEST study suggests this represents a significant issue, with 62% of surveyed GPs reporting no access to 'early arthritis clinics' (which streamline the referral process offering urgent appointments to patients with persistent synovitis), and 25% rating their ease of access to rheumatology as being ≤5 out of 10. This is despite evidence that the presence of early inflammatory arthritis clinics increasing the chances of a patients with new-onset inflammatory arthritis being seen within 3 weeks of referral [4].…”
Section: How Can We Support Gps To Improve the Early Diagnosis Of Infmentioning
confidence: 96%
“…In England and Wales, the benefits of early diagnosis and treatment have led to a Quality Standard from the National Institute for Health and Care Excellence that patients with suspected persistent synovitis are referred by GPs to specialists within 3-working days of presentation. A recent national audit has, however, demonstrated that this standard is met in only 17% of patients, with one-quarter waiting >3 months for referral [4]. For GPs, the challenge is to identify patients who potentially have an inflammatory arthritis from those who do not, at an early stage of their illness and refer them for urgent specialist review.…”
Section: Challenges In Identifying Inflammatory Arthritismentioning
confidence: 99%
“…Проведенный в 2016 году аудит показал лучшее соответствие выполняемых мероприятий совре-менным рекомендациям по лечению артритов [24].…”
Section: терминологияunclassified